Urgensi Motivasi Dalam Meningkatkan Semangat Belajar Siswa - Muhaemin B Muhaemin (Jurnal Adabiyah: Humanities and Islamic Studies, 2013)
Student motivation naturally has to do with students' desire to participate in the learning process. But it also concerns the reasons or goals that underline their involvement or noninvolvement in academic activities. Although students may be equally motivated to perform a task, the sources of their motivation may differ. When intrinsically motivated, students tend to employ strategies that demand more effort and that enable them to precede information more deeply. When students were confronted with complex intellectual tasks, those with an intrinsic orientation used more logical information-gathering and decision-making strategies than did students who were extrinsically oriented. Students with an intrinsic orientation also tend to prefer tasks that are moderately challenging, whereas extrinsically oriented students gravitate toward tasks that are low in degree of difficulty. Extrinsically oriented students are inclined to put forth the minimal amount of effort necessary to get the maximal reward.